Reliability and validity of SHMS v1.0 for suboptimal health status assessment of Tianjin residents and factors affecting sub-health: A cross-sectional study. Issue 17 (30th April 2021) - Miao, Jiameng; Liu, Ju; Wang, Yao; Zhang, Yuelin; Yuan, Hongxia
Abstract : Abstract: The study aimed to explore the reliability and validity of the Sub-Health Measurement Scale version 1.0 (SHMS v1.0) for the assessment of the suboptimal health status (SHS) of Tianjin residents. This was a cross-sectional study that surveyed 2640 urban residents in Tianjin from June 2016 to January 2018. Demographic and clinical characteristics were collected. Each subject completed the SHMS v1.0 and Short Form-36 (SF-36) scale assessments. The retest coefficient was 0.675. The overall Cronbach's α coefficient was 0.921. The correlation between SHMS v1.0 and SF-36 was 0.781 ( P < .01). The SHS frequency increased with age, from 62.4% in participants ⩽25 years of age to 72.8% in those ≥ 56 years of age. The multivariable analysis showed that female sex ( P < .001), age >25 years old ( P = .009), bachelor degree or above ( P < .001), obesity ( P < .0), regular smoking ( P = .043), frequent drinking ( P = .045), sleep time < 6 hours ( P = .006), working time >10 hours ( P < .001), physical exercise <5 times/mo ( P < .001), and adverse events >9 ( P < .001) were associated with SHS. The prevalence of SHS is high among urban residents in Tianjin. Abstract : Supplemental Digital Content is available in the text